2020
DOI: 10.1111/1750-3841.15422
|View full text |Cite
|
Sign up to set email alerts
|

Stability, kinetics, and application study of phycobiliprotein pigments extracted from red algae Gracilaria gracilis

Abstract: Phycobiliprotein (PBP) pigments were extracted from red algae Gracilaria gracilis through maceration in phosphate buffer using previously optimized conditions. The stability of PBPs in the extracts was assessed by monitoring the extracts at different pHs and temperatures for 10 days. Since phycoerythrin (PE) is the main PBP present in G. gracilis, PE content was spectroscopically determined and used as a response factor. Kinetic modeling was used to describe PE degradation under different ranges of T and pH. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
3
0
6
Order By: Relevance
“…Laver was red at the initial state because the PE pigment can reflect red light and absorb blue light (Bito et al, 2017). As a bioactive substance, phycobiliprotein was sensitive to temperature (Pereira, Barroso, Mendes, & Gil, 2020), resulting in a change from red to green after heating. Similarly, Miyamoto et al (2009) also found the phenomenon of red fading after laver was roasted.…”
Section: Resultsmentioning
confidence: 99%
“…Laver was red at the initial state because the PE pigment can reflect red light and absorb blue light (Bito et al, 2017). As a bioactive substance, phycobiliprotein was sensitive to temperature (Pereira, Barroso, Mendes, & Gil, 2020), resulting in a change from red to green after heating. Similarly, Miyamoto et al (2009) also found the phenomenon of red fading after laver was roasted.…”
Section: Resultsmentioning
confidence: 99%
“…Para la obtención de R-PE se analizaron tres métodos de extracción: maceración, maceración con sonda ultrasónica y maceración con baño ultrasónico (Pereira et al, 2020). Para todos los experimentos se utilizaron 0.1 g de biomasa liofilizada de P. cruentum, la cual se lavó con 10 mL de agua destilada y se homogenizó.…”
Section: Métodos De Extracciónunclassified
“…(2). Donde A 564 es la absorbancia máxima de R-PE y A 280 es la absorbancia de proteínas totales (Pereira et al, 2020) b Valores predichos de respuesta (RSM).…”
Section: Cuantificación De Ficobiliproteínasunclassified
See 2 more Smart Citations